2023
DOI: 10.1038/s41467-023-40098-z
|View full text |Cite|
|
Sign up to set email alerts
|

Characterization of crAss-like phage isolates highlights Crassvirales genetic heterogeneity and worldwide distribution

Abstract: Crassvirales (crAss-like phages) are an abundant group of human gut-specific bacteriophages discovered in silico. The use of crAss-like phages as human fecal indicators is proposed but the isolation of only seven cultured strains of crAss-like phages to date has greatly hindered their study. Here, we report the isolation and genetic characterization of 25 new crAss-like phages (termed crAssBcn) infecting Bacteroides intestinalis, belonging to the order Crassvirales, genus Kehishuvirus and, based on their genom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 72 publications
0
8
0
Order By: Relevance
“…Based on the experimental data mentioned above, we have reasons to speculate that pqsA mutation significantly inhibits the development of phage resistance. Literature reports have indicated that phase variation in receptor structure mediates the coexistence of phages and bacteria, maintaining a balance between host sensitivity and phage resistance ( Shkoporov et al., 2021 ; Ramos-Barbero et al., 2023 ). Growth curve analysis of phage-host cocultures revealed that, after 240 min, the wild-type PAO1 strain exhibited significant growth, while PaΔ pqsA remained suppressed ( Figures 1A , 2A , 4B ), suggesting that the pqsA mutant strain might have lost the ability to regulate flexible phase variation in receptor structure in the face of peak phage predation pressure, leading to a deficiency in bacterial immunity against phages compared to the wild-type strain PAO1.…”
Section: Resultsmentioning
confidence: 99%
“…Based on the experimental data mentioned above, we have reasons to speculate that pqsA mutation significantly inhibits the development of phage resistance. Literature reports have indicated that phase variation in receptor structure mediates the coexistence of phages and bacteria, maintaining a balance between host sensitivity and phage resistance ( Shkoporov et al., 2021 ; Ramos-Barbero et al., 2023 ). Growth curve analysis of phage-host cocultures revealed that, after 240 min, the wild-type PAO1 strain exhibited significant growth, while PaΔ pqsA remained suppressed ( Figures 1A , 2A , 4B ), suggesting that the pqsA mutant strain might have lost the ability to regulate flexible phase variation in receptor structure in the face of peak phage predation pressure, leading to a deficiency in bacterial immunity against phages compared to the wild-type strain PAO1.…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that certain groups of crAss-like phages dominate in industrialized countries, while other crAss-like phages are more common among the rural population of developing countries. The prevalence of crAss-like phages in the urban population is substantially higher than in the rural population [8,12,13]. This fact can be partly explained by the association of Bacteroides with the diet of the urban population [14].…”
Section: Introductionmentioning
confidence: 97%
“…Later, another 30 crAssphages were identified, cultivated, and studied that allowed them to be attributed to 11 different species of the Steigviridae family. Most of them infect Bacteroides intestinalis; three species infect Bacteroides cellulosilyticus and one is specific to Bacteroides tethaiotaomicron [7,8]. In 2021, the ΦCrAss002 phage belonging to the Jahgtovirus secundus species, the Intestiviridae family (former alpha group of сrAss-like phages) was isolated from Bacteroides xylanisolvens [5].…”
Section: Introductionmentioning
confidence: 99%
“…Later, another 30 crAssphages were identified, cultivated, and studied, which allowed them to be classified to 11 different species of the Steigviridae family. Most of them infect Bacteroides intestinalis ; however, three species infect Bacteroides cellulosilyticus , and one is specific to Bacteroides tethaiotaomicron [ 6 , 7 ]. In 2021, the ΦCrAss002 phage belonging to the Jahgtovirus secundus species and the Intestiviridae family (former Alpha group of crAss-like phages) was isolated from Bacteroides xylanisolvens [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that certain groups of crAss-like phages dominate in developed countries, while other crAss-like phages are more common among the rural populations of developing countries. The prevalence of crAss-like phages is substantially higher in the urban populations than in rural populations [ 6 , 12 , 13 ]. This fact can be partly explained by the association of Bacteroides with the diet of urban populations [ 14 ].…”
Section: Introductionmentioning
confidence: 99%